Design and application of a confocal microscope for spectrally resolved anisotropy imaging - Esposito, A.; Bader, A.N.; Schlachter, S.C.; van den Heuvel, D.J.; Kaminski Schierle, G.S.; Venkitaraman, A.R.; Kaminski, C.F.; Gerritsen, H.C. (The Optical Society, 2011)
Biophysical imaging tools exploit several properties of fluorescence to map cellular biochemistry. However, the engineering of a cost-effective and user-friendly detection system for sensing the diverse properties of fluorescence is a difficult challenge. Here, we present a novel architecture for a spectrograph that permits integrated characterization of excitation, emission and fluorescence anisotropy spectra in a quantitative and efficient manner. This sensing platform achieves excellent versatility of use at comparatively low costs. We demonstrate the novel optical design with example images of plant cells and of mammalian cells expressing fluorescent proteins undergoing energy transfer.